Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery

By using a mixture of Group 2 element oxide and silica in the negative electrode of the nonaqueous electrolyte secondary battery and combining an acrylic resin, the formation of hydrogen fluoride is suppressed, the problem of deterioration of silicon-containing materials is solved, and the battery is improved cycle characteristics and capacity maintenance.

CN113597686BActive Publication Date: 2024-12-20PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202080022100.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-03-19
Filing Date
2020-03-11
Publication Date
2024-12-20
Estimated Expiration
2040-03-11

AI Technical Summary

Technical Problem

In the prior art, silicon-containing materials are prone to deterioration in the negative electrode of a nonaqueous electrolyte secondary battery due to decomposition of hydrogen fluoride, resulting in a decrease in circulation characteristics.

Method used

The negative electrode mixture containing Group 2 element oxide and silica is used, and the alkaline shift of the negative electrode slurry is suppressed by adding acrylic resin, and the content of Group 2 element oxide is controlled to reduce hydrogen fluoride. Generation and dissolution of silicon-containing materials.

Benefits of technology

The circulation characteristics of the nonaqueous electrolyte secondary battery are significantly improved, the service life of the negative electrode is extended, and the high capacity performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113597686B_ABST
    Figure CN113597686B_ABST
Patent Text Reader

Abstract

The negative electrode for a non-aqueous electrolyte secondary battery comprises: a negative electrode mixture comprising a negative electrode active material capable of electrochemically absorbing and releasing lithium ions, a negative electrode additive, and an acrylic resin. The negative electrode active material comprises a silicon-containing material. The negative electrode additive comprises at least an oxide of a Group 2 element and silicon dioxide, and the oxide of the Group 2 element comprises at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO, and RaO. The acrylic resin comprises at least a unit of (meth)acrylate. Relative to the total amount of the negative electrode additive, the content of the oxide of the Group 2 element in the negative electrode additive is less than 20% by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode including a silicon-containing material and a non-aqueous electrolyte secondary battery having the negative electrode. Background Art

[0002] Non-aqueous electrolyte secondary batteries represented by lithium-ion secondary batteries have a positive electrode, a negative electrode, and a non-aqueous electrolyte. The negative electrode has: a negative electrode mixture containing a negative electrode active material that can electrochemically absorb and release lithium ions. In order to achieve high battery capacity, methods of using silicon-containing materials for negative electrode active materials are being studied. The non-aqueous electrolyte contains a lithium salt, and lithium hexafluorophosphate (LiPF6) can be widely used as the lithium salt.

[0003] Components in the non-aqueous electrolyte may react with water in the battery to form hydrogen fluoride. Hydrogen fluoride easily decomposes silicon-containing materials, and the cycle characteristics are likely to decrease due to the decomposition of silicon-containing materials.

[0004] In order to reduce hydrogen fluoride, Patent Document 1 proposes a method of adding glass powder containing silicon dioxide and an oxide of an alkaline earth metal to an anode or the like.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application No. 2015-532762 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] As a method of adding glass powder described in Patent Document 1, it is conceivable to use a negative electrode slurry prepared by dispersing a negative electrode mixture containing a silicon-containing material and glass powder in water to make a negative electrode. However, the negative electrode slurry containing glass powder tends to shift toward alkalinity, and the silicon-containing material will dissolve and deteriorate under alkalinity, and sometimes the cycle characteristics will be reduced.

[0010] Solutions for solving problems

[0011] In view of the above, one aspect of the present invention relates to a negative electrode for a non-aqueous electrolyte secondary battery, comprising: a negative electrode mixture comprising a negative electrode active material capable of electrochemically storing and releasing lithium ions, a negative electrode additive and an acrylic resin; the aforementioned negative electrode active material comprises a silicon-containing material; the aforementioned negative electrode additive comprises at least an oxide of a Group 2 element and silicon dioxide; the aforementioned oxide of the Group 2 element comprises at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO and RaO; the aforementioned acrylic resin comprises at least a unit of (meth)acrylate; relative to the total amount of the aforementioned negative electrode additive, the content of the aforementioned oxide of the Group 2 element in the aforementioned negative electrode additive is less than 20% by mass.

[0012] In another aspect, the present invention relates to a nonaqueous electrolyte secondary battery comprising a positive electrode and a negative electrode and a nonaqueous electrolyte, wherein the negative electrode is the negative electrode described above.

[0013] Effects of the Invention

[0014] According to the present invention, the cycle characteristics of a non-aqueous electrolyte secondary battery including a negative electrode including a silicon-containing material can be improved.

[0015] The configuration and content of the present invention can be further understood from other objects and features of the present invention through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic perspective view showing a portion of a non-aqueous electrolyte secondary battery in cross section according to an embodiment of the present invention. DETAILED DESCRIPTION

[0017] A negative electrode for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention comprises: a negative electrode mixture comprising a negative electrode active material capable of electrochemically storing and releasing lithium ions, a negative electrode additive, and an acrylic resin. The negative electrode active material comprises a silicon-containing material. The negative electrode additive comprises at least an oxide of a Group 2 element and silicon dioxide, and the oxide of the Group 2 element comprises at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO, and RaO. The acrylic resin comprises at least a unit of (meth)acrylate. Relative to the total amount of the negative electrode additive (100% by mass), the content of the oxide of the Group 2 element in the negative electrode additive is less than 20% by mass.

[0018] By making the negative electrode mixture contain the above-mentioned negative electrode additive, the degradation of the silicon-containing material caused by hydrogen fluoride generated during charging and discharging after the battery is manufactured is suppressed. In addition, by adjusting the content of the oxide of the second element in the negative electrode additive to the above-mentioned range, and making the negative electrode mixture contain the above-mentioned acrylic resin, the shift of the negative electrode slurry to alkalinity caused by the negative electrode additive is greatly suppressed. By suppressing the shift of the negative electrode slurry to alkalinity, the dissolution degradation of the silicon-containing material and the reduction of the cycle characteristics caused by the degradation are greatly suppressed.

[0019] (Negative electrode additives)

[0020] The negative electrode additive contains at least: silicon dioxide (SiO2); and an oxide of at least one Group 2 element selected from the group consisting of BeO, MgO, CaO, SrO, BaO and RaO. Hydrogen fluoride generated by the decomposition of the non-aqueous electrolyte caused by the water in the battery reacts with the silicon dioxide and the oxide of the Group 2 element in the negative electrode additive to generate fluoride. The amount of hydrogen fluoride is reduced by the negative electrode additive, so that the dissolution degradation of the silicon-containing material is suppressed and the cycle characteristics are improved. For example, when BaO is used, BaSiF6 is generated. The negative electrode additive can be used, for example, in the form of a powdered glass containing an oxide of a Group 2 element and silicon dioxide.

[0021] In the above-mentioned negative electrode additive, when the content of the oxide of the Group 2 element is less than 20% by mass relative to the total amount of the negative electrode additive, hydrogen fluoride can be fully absorbed and the shift of the negative electrode slurry to alkalinity can be suppressed, thereby reducing the dissolution degradation of the silicon-containing material. When a negative electrode additive containing both the above-mentioned acrylic resin and a specific amount of the oxide of the Group 2 element is used, the cycle characteristics are greatly improved.

[0022] Relative to the total amount of the negative electrode additive, the content of the oxide of the Group 2 element in the negative electrode additive is, for example, 1% by mass or more and less than 20% by mass, preferably 3% by mass or more and 19.5% by mass or less, more preferably 10% by mass or more and 19.5% by mass or less. Relative to the total amount of the negative electrode additive, when the content of the oxide of the Group 2 element in the negative electrode additive is 1% by mass or more, hydrogen fluoride is fully absorbed by the negative electrode additive. Relative to the total amount of the negative electrode additive, when the content of the oxide of the Group 2 element in the negative electrode additive is less than 20% by mass, the Group 2 element contained in the negative electrode additive is difficult to dissolve in the negative electrode slurry (dispersion medium) in the form of ions, and the shift of the negative electrode slurry to alkalinity is suppressed. In addition, the Group 2 element is easy to exist in the form of an oxide in the negative electrode slurry, so the absorption effect of hydrogen fluoride can be fully obtained.

[0023] The content of the oxide of the Group 2 element in the negative electrode additive (mass ratio relative to the total amount of the negative electrode additive) can be determined by the following method.

[0024] The battery is disassembled, the negative electrode is taken out, and after cleaning and drying with a non-aqueous solvent such as ethylene carbonate, the cross-section of the negative electrode mixture layer is processed using a cross-section polisher (CP) to obtain a sample. A field emission scanning electron microscope (FE-SEM) is used to obtain a reflected electron image of the sample cross section and observe the cross section of the negative electrode additive particles. An Auger electron spectroscopy (AES) analysis device is used to perform qualitative and quantitative element analysis on a certain area in the central part of the cross section of the observed negative electrode additive particles to determine the mass of the Group 2 element M (acceleration voltage 10kV, beam current 10nA). Assuming that all Group 2 elements M are oxides MO, the M amount obtained by the above analysis is converted into the MO amount. The 10 observed negative electrode additive particles are analyzed, and the average value of the calculated MO amount is set as the mass W1 of the oxide of the Group 2 element.

[0025] In the above analysis, the mass of the Group 2 element M and the mass of other elements Q (alkali metal elements such as Si, Na, Al, etc.) other than the Group 2 element M are obtained. Assuming that all elements Q are oxides of element Q (SiO2, Na2O, Al2O3, etc.), the mass of element Q is converted to the mass of the oxide of element Q. The 10 observed negative electrode additive particles are analyzed, and the average value of the calculated mass of the oxide of element Q is set as the mass W2 of the oxide of element Q. The total value of W1 and W2 is set as the total amount W0 of the negative electrode additive.

[0026] (W1 / W0)×100 was calculated and set as the content of the oxide of the Group 2 element in the negative electrode additive (mass ratio relative to the total amount of the negative electrode additive).

[0027] It should be noted that the average particle size of the negative electrode additive particles (about 0.3 μm or more and 3 μm or less) is larger than that of the silicon-containing material (SiO x , LSX) particles have a small average particle size (about 5 μm or more and about 10 μm or less), and silicon particles are dispersed inside the particles of the silicon-containing material. By observing the particle size and the inside of the particles, the negative electrode additive particles and the silicon-containing material can be distinguished. That is, the negative electrode additive can be silicate particles or glass particles that do not contain silicon particles. In the cross-sectional observation and analysis of the above-mentioned samples, in order to prevent the diffusion of Li, a carbon sample stand can be used to fix the sample. In order to prevent the cross-section of the sample from being deteriorated, a transfer container that does not expose the sample to the atmosphere and is maintained and transported can be used.

[0028] The total content of silicon dioxide and oxides of Group 2 elements in the negative electrode additive is, for example, 80% by mass or more, or 85% by mass or more relative to the total amount of the negative electrode additive. In the negative electrode additive, the mass ratio of oxides of Group 2 elements to silicon dioxide is, for example, 1 / 3 or more and 50 or less.

[0029] The oxide of the Group 2 element preferably contains at least one selected from the group consisting of BaO and CaO. In this case, a significant effect of capturing hydrogen fluoride can be obtained, and the cycle characteristics are further improved.

[0030] The negative electrode additive may further include an oxide of an alkali metal element. In addition, the negative electrode additive may further include other components such as Al2O3, B2O3, P2O5, etc. The oxide of an alkali metal element may also include at least one selected from the group consisting of Li2O, Na2O and K2O. Among them, the oxide of an alkali metal element is preferably Na2O.

[0031] When the negative electrode additive also contains Na2O, the cycle characteristics are easy to be further improved. At this time, Na is easy to dissolve from the negative electrode additive into the electrolyte, and the reaction activity of the negative electrode additive in which Na is dissolved becomes higher, and it is easy to react with hydrogen fluoride to form fluoride, so that the dissolution and degradation of the silicon-containing material caused by hydrogen fluoride is more effectively suppressed. In addition, Na dissolved from the negative electrode additive may become a constituent component of the SEI (Solid Electrolyte Interphase) film formed on the surface of the negative electrode active material as charging and discharging. Compared with the SEI film of Li alone, the resistance of the SEI film containing both Li and Na is easy to reduce. Based on the above, it can be inferred that the cycle characteristics are easier to improve.

[0032] Relative to the total amount (100% by mass) of the negative electrode mixture, the content of the negative electrode additive in the negative electrode mixture is less than 8% by mass, preferably less than 7% by mass, more preferably more than 0.3% by mass and less than 7% by mass, and further preferably more than 0.4% by mass and less than 2% by mass. Relative to the total amount of the negative electrode mixture, when the content of the negative electrode additive in the negative electrode mixture is more than 0.3% by mass, it is easy to obtain the capture effect of hydrogen fluoride. Relative to the total amount of the negative electrode mixture, when the content of the negative electrode additive in the negative electrode mixture is less than 7% by mass, it is easy to obtain the capture effect of hydrogen fluoride and the inhibitory effect of the shift of the negative electrode slurry to alkalinity with good balance.

[0033] The content of the negative electrode additive in the negative electrode mixture (the amount relative to the total amount of the negative electrode mixture) can be obtained by the following method. For example, the negative electrode additive can be separated from a sample of the negative electrode mixture with a known mass, and its mass can be obtained, thereby obtaining the proportion of the sample of the negative electrode mixture. The negative electrode additive particles and the mixture of the negative electrode additive particles and the silicon-containing material particles can be separated from the negative electrode mixture by a known method.

[0034] Similar to the case of determining the content of the oxide of the Group 2 element in the negative electrode additive mentioned above, the mass ratio of the negative electrode additive particles to the silicon-containing material particles can also be determined using an image of the sample cross section (reflected electron image, etc.). By observing the particle size and the inside of the particles, the negative electrode additive particles and the silicon-containing material particles are distinguished, and the area ratio of the negative electrode additive particles to the silicon-containing material particles is determined. The composition of the negative electrode additive is determined by AES analysis. For silicon-containing materials, the composition of the matrix phase is determined by AES analysis, and the content of silicon particles dispersed in the matrix phase is determined by Si-NMR. The specific gravity of each material is determined based on the composition. Based on the values ​​obtained above, the content of the negative electrode additive in the negative electrode mixture is determined. It should be noted that the area ratio of the negative electrode additive particles to the silicon-containing material particles can also be regarded as a volume ratio.

[0035] (Acrylic resin)

[0036] The acrylic resin contains at least a unit of (meth)acrylate. It should be noted that, in this specification, the meaning of "(meth)acrylic acid" is at least one selected from the group consisting of "acrylic acid" and "methacrylic acid". In the negative electrode slurry, the acrylic resin may contain both units of (meth)acrylic acid and units of (meth)acrylate. (Meth)acrylic acid is a weak acid, and (meth)acrylate is a salt of a weak acid, so for alkaline negative electrode additives, acrylic resins can play a buffering role. Therefore, the shift of the negative electrode slurry to alkalinity caused by the negative electrode additive is suppressed. Acrylic resins can also serve as a binder in the negative electrode mixture and play a role.

[0037] The ratio of hydrogen atoms of carboxyl groups in the acrylic resin to be replaced by alkali metal atoms (hereinafter referred to as substitution rate) is preferably 70% or more and 80% or less, and more preferably 90% or more. When the negative electrode slurry contains an acrylic resin with a substitution rate in the above range, the buffering effect based on the acrylic resin is easy to exert, and the deviation of the negative electrode slurry to alkalinity caused by the negative electrode additive is effectively suppressed. In addition, it is easy to prepare the negative electrode slurry, which is conducive to the improvement of battery characteristics.

[0038] Examples of the (meth)acrylic acid salt include alkali metal salts such as lithium salts and sodium salts, and ammonium salts. Among them, lithium salts of (meth)acrylic acid are preferred, and lithium salts of acrylic acid are more preferred, from the viewpoint of reducing internal resistance.

[0039] More specifically, the acrylic resin is a polymer containing at least a unit of (meth)acrylic acid and a unit of (meth)acrylate among the units of (meth)acrylate. The polymer may also contain at least only a unit of (meth)acrylic acid and a unit of (meth)acrylate among the units of (meth)acrylate as a repeating unit. The polymer may also contain other units other than the units of (meth)acrylic acid and the units of (meth)acrylate. Examples of other units include ethylene units. In the polymer, the total amount of the units of (meth)acrylic acid and the units of (meth)acrylate is, for example, preferably 50 mol% or more, and more preferably 80 mol% or more.

[0040] Specific examples of acrylic resins include salts (substitution rate 90% or more) of polyacrylic acid, polymethacrylic acid, copolymers containing repeating units of acrylic acid and / or methacrylic acid (acrylic acid-methacrylic acid copolymers, ethylene-acrylic acid copolymers, etc.), etc. These may be used alone or in combination of two or more.

[0041] The weight average molecular weight of the acrylic resin is preferably greater than or equal to 3000 and less than or equal to 10000000. When the weight average molecular weight of the acrylic resin is within the above range, the cycle characteristics of the acrylic resin can be sufficiently improved and the internal resistance can be reduced, and the gelation (viscosity increase) of the negative electrode slurry is suppressed, making it easy to prepare the negative electrode.

[0042] The content of acrylic resin in the negative electrode mixture can be 0.2 mass parts or more and 2 mass parts or less, or 0.4 mass parts or more and 1.5 mass parts or less per 100 mass parts of negative electrode active material. When the content of acrylic resin in the negative electrode mixture is 0.2 mass parts or more per 100 mass parts of negative electrode active material, the effect of suppressing the deviation of the negative electrode mixture to alkalinity can be fully obtained. When the content of acrylic resin in the negative electrode mixture is 2 mass parts or less per 100 mass parts of negative electrode active material, the increase of contact resistance between the negative electrode active material particles and between the negative electrode active material particles (negative electrode mixture layer) and the negative electrode collector with repeated charge and discharge is suppressed. In addition, the viscosity of the negative electrode slurry can be reduced, and the negative electrode slurry can be easily prepared. The amount of negative electrode active material is fully ensured and easy to be high-capacitance.

[0043] (Negative electrode active material)

[0044] The negative electrode active material includes a silicon-containing material that can electrochemically store and release lithium ions. The silicon-containing material is advantageous for increasing the capacity of the battery.

[0045] (First composite material)

[0046] The silicon-containing material may also be a first composite material having a silicate phase and silicon particles dispersed in the silicate phase, wherein the silicate phase comprises at least one selected from the group consisting of alkali metal elements and group 2 elements. By controlling the amount of silicon particles dispersed in the silicate phase, further high capacity can be achieved. The silicon particles are dispersed in the silicate phase, so that the expansion and contraction of the first composite material during charge and discharge is suppressed. Therefore, the first composite material is beneficial to the high capacity and cycle characteristics of the battery.

[0047] Hereinafter, the first composite material will be described in detail.

[0048] (Silicon particles)

[0049] From the viewpoint of suppressing cracking of the silicon particles themselves, before the initial charge, the average particle size of the silicon particles is preferably 500 nm or less, more preferably 200 nm or less, and further preferably 50 nm or less. After the initial charge, the average particle size of the silicon particles is preferably 400 nm or less, and more preferably 100 nm or less. By miniaturizing the silicon particles, the volume change during charge and discharge becomes smaller, and the structural stability of the first composite material is further improved.

[0050] The average particle size of the silicon particles is measured by observing a cross-sectional SEM (scanning electron microscope) photograph of the first composite material. Specifically, the average particle size of the silicon particles can be determined by taking the average value of the maximum diameters of any 100 silicon particles.

[0051] From the viewpoint of high capacity, the content of silicon particles in the first composite material is preferably 30% by mass or more, more preferably 35% by mass or more, and further preferably 55% by mass or more. At this time, the diffusivity of lithium ions is good, and it is easy to obtain excellent load characteristics. On the other hand, from the viewpoint of improving cycle characteristics, the content of silicon particles in the first composite material is preferably 80% by mass or less, and further preferably 70% by mass or less. At this time, the surface of silicon particles that are not covered by the silicate phase and exposed is reduced, and it is easy to suppress the reaction of the electrolyte and the silicon particles.

[0052] The content of silicon particles can be measured by Si-NMR. The following shows the ideal measurement conditions of Si-NMR.

[0053] Measuring device: Varian, Inc., solid-state nuclear magnetic resonance spectrometer (INOVA-400)

[0054] Probe: Varian 7mm CPMAS-2

[0055] MAS: 4.2kHz

[0056] MAS speed: 4kHz

[0057] Pulse: DD (45° pulse + signal capture time 1H decoupling)

[0058] Repeat time: 1200 seconds

[0059] Observation width: 100kHz

[0060] Observation center: around -100ppm

[0061] Signal capture time: 0.05 seconds

[0062] Cumulative number of times: 560

[0063] Sample volume: 207.6 mg

[0064] The silicon particles dispersed in the silicate phase have a granular phase of silicon (Si) alone and are composed of a single or multiple crystallites. The crystallite size of the silicon particles is preferably less than 30 nm. When the crystallite size of the silicon particles is less than 30 nm, the volume change caused by the expansion and contraction of the silicon particles accompanying charge and discharge can be reduced, and the cycle characteristics are further improved. For example, when the silicon particles shrink, gaps are formed around the silicon particles, and the contact points between the particles and the surroundings are reduced, thereby suppressing the isolation of the particles, and suppressing the reduction in charge and discharge efficiency caused by the isolation of the particles. The lower limit of the crystallite size of the silicon particles is not particularly limited, for example, it is greater than 5 nm.

[0065] In addition, the crystallite size of the silicon particles is more preferably 10 nm or more and 30 nm or less, and further preferably 15 nm or more and 25 nm or less. When the crystallite size of the silicon particles is 10 nm or more, the surface area of ​​the silicon particles can be suppressed to be small, so it is difficult to produce the degradation of the silicon particles accompanied by the generation of irreversible capacity.

[0066] The crystallite size of the silicon particles is calculated by the Scherrer equation from the half-value width of the diffraction peak attributed to the Si (111) plane in the X-ray diffraction (XRD) pattern of the silicon particles.

[0067] (Silicate phase)

[0068] The silicate phase contains at least one of an alkali metal element (a Group 1 element other than hydrogen in the long-period periodic table) and a Group 2 element in the long-period periodic table. Alkali metal elements include lithium (Li), potassium (K), sodium (Na), etc. Group 2 elements include magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. The silicate phase contains at least: at least one element of an alkali metal element and a Group 2 element; silicon (Si); and oxygen (O). The silicate phase may also contain aluminum (Al), boron (B), lanthanum (La), phosphorus (P), zirconium (Zr), titanium (Ti), iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), zinc (Zn), etc. as other elements.

[0069] From the perspective of small irreversible capacity and high initial charge and discharge efficiency, the silicate phase is preferably a silicate phase containing lithium (hereinafter also referred to as a lithium silicate phase). That is, the first composite material preferably comprises a composite material of a lithium silicate phase and silicon particles dispersed in the lithium silicate phase (hereinafter also referred to as LSX or negative electrode material LSX). The lithium silicate phase contains at least lithium (Li), silicon (Si) and oxygen (O). The atomic ratio of O to Si in the lithium silicate phase: O / Si is, for example, greater than 2 and less than 4. When O / Si is greater than 2 and less than 4 (z in the formula described below is 0<z<2), it is advantageous from the perspective of stability and lithium ion conductivity. Preferably, O / Si is greater than 2 and less than 3 (z in the formula described below is 0<z<1). The atomic ratio of Li to Si in the lithium silicate phase: Li / Si is, for example, greater than 0 and less than 4. In addition to Li, Si and O, the lithium silicate phase may also contain the above-mentioned other elements.

[0070] The lithium silicate phase may, for example, have the formula: Li 2z SiO 2+z The composition is represented by (0<z<2). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z preferably satisfies the relationship of 0<z<1, and z=1 / 2 is more preferred.

[0071] The lithium silicate phase of LSX and SiO x Compared with the SiO2 phase, LSX has fewer sites that can react with lithium. x In comparison, it is difficult to generate irreversible capacity accompanying charge and discharge. When silicon particles are dispersed in the lithium silicate phase, excellent charge and discharge efficiency can be obtained at the beginning of charge and discharge. In addition, the content of silicon particles can be arbitrarily changed, so a high-capacity negative electrode can be designed.

[0072] The composition of the lithium silicate phase of the negative electrode material LSX can be analyzed, for example, by the following method.

[0073] The battery is disassembled, the negative electrode is taken out, and after cleaning and drying with a non-aqueous solvent such as ethylene carbonate, the cross-section of the negative electrode mixture layer is processed using a cross-section polisher (CP) to obtain a sample. A field emission scanning electron microscope (FE-SEM) is used to obtain a reflected electron image of the sample cross section and observe the cross section of the LSX particles. An Auger electron spectroscopy (AES) analysis device is used to perform qualitative and quantitative elemental analysis of the lithium silicate of the observed LSX particles (acceleration voltage 10kV, beam current 10nA). Based on the obtained contents of lithium (Li), silicon (Si), oxygen (O), and other elements, the composition of the lithium silicate phase is determined.

[0074] It should be noted that the average particle size of LSX particles (about 5 μm or more and 10 μm or less) is larger than the average particle size of negative electrode additive particles (about 0.3 μm or more and 3 μm or less), and silicon particles are dispersed inside the LSX particles. Therefore, LSX particles and negative electrode additive particles can be distinguished by observing the particle size and the inside of the particles.

[0075] In the above-mentioned cross-sectional observation and analysis of the sample, a carbon sample stand may be used to fix the sample in order to prevent the diffusion of Li. In order to prevent the cross-sectional quality of the sample from being altered, a transfer container may be used that holds and transports the sample without exposing it to the atmosphere.

[0076] The first composite material is preferably formed into a granular material (hereinafter also referred to as the first particle) having an average particle size of 5 μm or more and 25 μm or less, and more preferably 7 μm or more and 15 μm or less. When the particle size range is as described above, it is easy to relax the stress caused by the volume change of the first composite material accompanying charge and discharge, and it is easy to obtain good cycle characteristics. The surface area of ​​the first particle also becomes appropriate, and the capacity reduction caused by the side reaction with the electrolyte is also suppressed.

[0077] The average particle size of the first particles means a particle size (volume average particle size) at which the volume cumulative value is 50% in a particle size distribution measured by a laser diffraction scattering method. For example, a measuring device such as "LA-750" manufactured by HORIBA Ltd. can be used.

[0078] The first particle preferably has a conductive material covering at least a portion of its surface. The silicate phase lacks electronic conductivity, so the conductivity of the first particle tends to decrease. By covering the surface with a conductive material, the conductivity can be greatly improved. The conductive layer is preferably thick enough not to substantially affect the average particle size of the first particle.

[0079] (Second composite material)

[0080] The silicon-containing material may also be a second composite material having a SiO2 phase and silicon particles dispersed in the SiO2 phase. The second composite material is represented by SiOx, and satisfies 0<x<2. X may be greater than 0.5 and less than 1.5. The second composite material is advantageous in that it has a small expansion during charging.

[0081] (Carbon material)

[0082] The negative electrode active material may also include a carbon material that electrochemically absorbs and releases lithium ions. Compared with silicon-containing materials, carbon materials have a smaller degree of expansion and contraction during charge and discharge. By using silicon-containing materials and carbon materials in combination, the contact state between the negative electrode active material particles and between the negative electrode mixture layer and the negative electrode collector can be better maintained during repeated charge and discharge. That is, the high capacity of the silicon-containing material can be imparted to the negative electrode and the cycle characteristics can be improved. From the viewpoint of high capacity and improved cycle characteristics, the proportion of carbon material in the total of silicon-containing materials and carbon materials is preferably less than 98% by mass, more preferably greater than 70% by mass and less than 98% by mass, and further preferably greater than 75% by mass and less than 95% by mass.

[0083] As the carbon material used in the negative electrode active material, examples include graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon). Among them, graphite with excellent charge and discharge stability and low irreversible capacity is preferred. Graphite means a material with a graphite-type crystal structure, including, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon material may be used alone, or two or more may be used in combination.

[0084] (Non-aqueous electrolyte secondary battery)

[0085] The nonaqueous electrolyte secondary battery according to the embodiment of the present invention includes a positive electrode, a negative electrode, and a nonaqueous electrolyte, and the negative electrode may include the negative electrode mixture described above.

[0086] Hereinafter, the nonaqueous electrolyte secondary battery will be described in detail.

[0087] [negative electrode]

[0088] The negative electrode may also include a negative electrode collector and a negative electrode mixture layer supported on the surface of the negative electrode collector. The negative electrode mixture layer can be formed by dispersing a negative electrode mixture comprising a silicon-containing material, a negative electrode additive and an acrylic resin in water to prepare a negative electrode slurry, applying the negative electrode slurry on the surface of the negative electrode collector, and drying it. By making the negative electrode mixture (negative electrode slurry) contain an acrylic resin, the deviation of the negative electrode slurry toward alkalinity caused by the negative electrode additive is suppressed. The dried coating film may also be rolled as needed. The negative electrode mixture layer may be formed on one surface of the negative electrode collector or on both surfaces.

[0089] The negative electrode mixture contains a negative electrode active material, a negative electrode additive and an acrylic resin as essential components. The negative electrode mixture may contain a binder, a conductive agent, a thickener, etc. other than the acrylic resin as optional components. The negative electrode active material contains at least a silicon-containing material and may also contain a carbon material.

[0090] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, mesh, punched sheet, etc.) can be used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified. The thickness of the negative electrode current collector is not particularly limited, but from the perspective of balancing the strength and lightness of the negative electrode, it is preferably 1 to 50 μm, and 5 to 20 μm is more ideal.

[0091] Examples of binders other than acrylic resins include fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resins; polyimide resins such as polyimide and polyamide-imide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymers; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinyl pyrrolidone; polyether sulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. The binders other than acrylic resins may be used alone or in combination of two or more.

[0092] Examples of the conductive agent include carbons such as acetylene black and carbon nanotubes; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; organic conductive materials such as benzene derivatives, etc. The conductive agent may be used alone or in combination of two or more.

[0093] Examples of thickeners include carboxymethyl cellulose (CMC) and modified forms thereof (including salts such as Na salts), cellulose derivatives such as methyl cellulose (cellulose ethers, etc.), saponified polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide), etc. The thickeners may be used alone or in combination of two or more.

[0094] As the dispersion medium of the negative electrode slurry, a polar dispersion medium can be used, such as water, alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, and N-methyl-2-pyrrolidone (NMP). The dispersion medium can be used alone or in combination of two or more.

[0095] [positive electrode]

[0096] The positive electrode may, for example, include a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer may be formed by applying a positive electrode slurry in which a positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it. The dried coating may also be rolled as needed. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces. The positive electrode mixture contains a positive electrode active material as an essential component and may contain a binder, a conductive agent, etc. as arbitrary components. As a dispersion medium for the positive electrode slurry, those exemplified in the negative electrode slurry may be used.

[0097] As the positive electrode active material, for example, a lithium-containing composite oxide can be used. For example, Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4、Li a Mn 2-b M b O4, LiMPO4, Li2MPO4F (M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B.) Here, a=0 to 1.2, b=0 to 0.9, and c=2.0 to 2.3. It should be noted that the value a showing the molar ratio of lithium increases or decreases with charge and discharge.

[0098] Among them, Li is preferred a Ni b M 1-b A lithium nickel composite oxide represented by O2 (M is at least one selected from the group consisting of Mn, Co and Al, 0<a≤1.2, 0.3≤b≤1.) is preferred to satisfy 0.85≤b≤1 from the viewpoint of high capacity. Lithium nickel composite oxide containing Co and Al as M is further preferred from the viewpoint of crystal structure stability. a Ni b Co c Al d O2 (0<a≤1.2, 0.85≤b<1, 0<c<0.15, 0<d≤0.1, b+c+d=1).

[0099] As the binder and the conductive agent, the same ones as those exemplified in the negative electrode can be used. As the binder, an acrylic resin can also be used. As the conductive agent, graphite such as natural graphite and artificial graphite can also be used.

[0100] The shape and thickness of the positive electrode current collector can be selected according to the shape and range of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, and the like.

[0101] [Non-aqueous electrolyte]

[0102] The non-aqueous electrolyte solution includes a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The concentration of the lithium salt in the non-aqueous electrolyte solution is preferably, for example, 0.5 mol / L or more and 2 mol / L or less. By setting the lithium salt concentration to the above range, a non-aqueous electrolyte solution having excellent ion conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.

[0103] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 , lithium lower aliphatic carboxylates, LiCl, LiBr, LiI, borates, imide salts, etc. Examples of borates include lithium bis(1,2-benzenediolate (2-)-O,O')borate, lithium bis(2,3-naphthalenediolate (2-)-O,O')borate, lithium bis(2,2'-biphenylediolate (2-)-O,O')borate, and lithium bis(5-fluoro-2-olate-1-benzenesulfonic acid-O,O')borate. Examples of imide salts include lithium bis(fluorosulfonyl)imide (LFSI), lithium bistrifluoromethanesulfonate imide (LiN(CF3SO2)2), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF3SO2)(C4F9SO2)), and lithium bispentafluoroethanesulfonate imide (LiN(C2F5SO2)2). Among these, LiPF6 is preferred. LiPF6 easily forms a passivation film on the surface of components constituting the battery, such as the outer can. The passivation film can protect the above components. The lithium salt can be used alone or in combination of two or more.

[0104] As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, etc. can be used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be mentioned. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be mentioned. As cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be mentioned. As chain carboxylates, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, etc. can be mentioned. The non-aqueous solvent can be used alone or in combination of two or more.

[0105] [Separator]

[0106] Generally, it is desirable to insert a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.

[0107] As an example of the structure of a non-aqueous electrolyte secondary battery, an electrode group in which a positive electrode and a negative electrode are wound with a separator and a non-aqueous electrolyte is contained in an outer shell can be cited. Alternatively, other electrode groups such as a stacked electrode group in which a positive electrode and a negative electrode are stacked with a separator can be used instead of a wound electrode group. The non-aqueous electrolyte secondary battery can be, for example, cylindrical, square, coin-shaped, button-shaped, laminated, etc.

[0108] Below, refer to Figure 1 The structure of a rectangular nonaqueous electrolyte secondary battery as an example of the nonaqueous electrolyte secondary battery of the present invention will be described. Figure 1 This is a schematic perspective view showing a portion of a non-aqueous electrolyte secondary battery in cross section according to an embodiment of the present invention.

[0109] The battery comprises a square-bottomed battery case 4 and an electrode group 1 and an electrolyte (not shown) contained in the battery case 4. The electrode group 1 comprises a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator inserted between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, the positive electrode, and the separator around a flat winding core and pulling out the winding core.

[0110] One end of the negative lead 3 is mounted on the negative electrode collector of the negative electrode by welding or the like. The other end of the negative lead 3 is electrically connected to the negative terminal 6 provided on the sealing plate 5 by means of a resin insulating plate (not shown). The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive lead 2 is mounted on the positive electrode collector of the positive electrode by welding or the like. The other end of the positive lead 2 is connected to the back of the sealing plate 5 by means of an insulating plate. That is, the positive lead 2 is electrically connected to the battery case 4 which also serves as the positive terminal. The insulating plate isolates the electrode group 1 from the sealing plate 5 and isolates the negative lead 3 from the battery case 4. The periphery of the sealing plate 5 is fitted with the open end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed by the sealing plate 5. The injection hole for the electrolyte provided in the sealing plate 5 is blocked by the sealing plug 8.

[0111] Example

[0112] Hereinafter, examples of the present invention will be described in detail, but the present invention is not limited to the following examples.

[0113] 《Example 1》

[0114] [Production of negative electrode]

[0115] After adding water to the negative electrode mixture, a mixer (manufactured by PRIMIX Corporation, TKHIVIS MIX) was used to stir the mixture to prepare a negative electrode slurry. The negative electrode mixture used a mixture of a negative electrode active material, a negative electrode additive, polyacrylic acid lithium salt (PAA-Li), sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR).

[0116] The negative electrode active material used was a mixture of a silicon-containing material and graphite, with the ratio of graphite to the total of the silicon-containing material and graphite being 95% by mass. Among the silicon-containing material, SiO (x=1) particles (average particle size 5 to 10 μm) were used as the second composite material.

[0117] The negative electrode additive uses powdered glass (average particle size 1 μm) containing silicon dioxide (SiO2), Li2O belonging to the oxide of alkali metal elements, and CaO belonging to the oxide of Group 2 elements. The contents of SiO2, Li2O and CaO in the negative electrode additive are set to 74.4 mass%, 8.2 mass% and 17.4 mass%, respectively. It should be noted that "Bal." of the SiO2 content in Tables 1 to 3 represents the remainder. The content of the negative electrode additive in the negative electrode mixture is set to 0.5 mass parts per 100 mass parts of negative electrode active material.

[0118] The PAA-Li substitution rate is 100%. The content of PAA-Li in the negative electrode mixture is set to 0.7 parts by mass per 100 parts by mass of the negative electrode active material. The content of CMC-Na in the negative electrode mixture is set to 1 part by mass per 100 parts by mass of the negative electrode active material. The content of SBR in the negative electrode mixture is set to 1 part by mass per 100 parts by mass of the negative electrode active material.

[0119] Then, every 1m 2 The negative electrode slurry was applied so that the mass of the negative electrode mixture on the surface of the copper foil was 190 g, and the coating was dried and then rolled to form a copper foil with a density of 1.5 g / cm on both sides. 3 A negative electrode mixture layer is formed to obtain a negative electrode.

[0120] [Production of positive electrode]

[0121] The lithium nickel composite oxide (LiNi 0.8 Co 0.18 Al 0.02 O2), acetylene black and polyvinylidene fluoride, add N-methyl-2-pyrrolidone (NMP), and stir using a mixer (made by PRIMIX Corporation, TKHIVIS MIX) to prepare positive electrode slurry. Next, the positive electrode slurry is applied to the surface of the aluminum foil, and the coating is dried and then rolled to form a density of 3.6 g / cm on both sides of the aluminum foil. 3 A positive electrode mixture layer is formed to obtain a positive electrode.

[0122] [Preparation of non-aqueous electrolyte]

[0123] A non-aqueous electrolyte solution was prepared by dissolving a lithium salt in a non-aqueous solvent. The non-aqueous solvent used was a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 3:7. LiPF6 was used as the lithium salt. The concentration of LiPF6 in the non-aqueous electrolyte solution was set to 1.0 mol / L.

[0124] [Manufacturing of non-aqueous electrolyte secondary battery]

[0125] The electrode group was prepared by installing a tab on each electrode, and winding the positive electrode and the negative electrode into a spiral shape with the tab located at the outermost periphery with the aid of a separator. The electrode group was inserted into an outer casing made of an aluminum laminate film, vacuum dried at 105° C. for 2 hours, and then injected with a nonaqueous electrolyte, and the opening of the outer casing was sealed to obtain a battery A1.

[0126] The negative electrode slurry and battery prepared above were evaluated as follows.

[0127] [Evaluation 1: pH of negative electrode slurry]

[0128] A negative electrode slurry used in preparing the battery A1 was prepared, and the pH of the negative electrode slurry at 25° C. was measured.

[0129] [Evaluation 2: Capacity retention rate at 150 cycles]

[0130] Battery A1 was charged at a constant current of 0.3 It (990 mA) to a voltage of 4.2 V, and then charged at a constant voltage of 4.2 V to a current of 0.015 It (50 mA). Thereafter, it was discharged at a constant current of 0.3 It (990 mA) to a voltage of 2.75 V. The pause time between charging and discharging was set to 10 minutes. Charging and discharging were performed at 25°C.

[0131] The charge and discharge were repeated under the above conditions. The capacity retention rate was calculated as the ratio of the discharge capacity at the 150th cycle to the discharge capacity at the 1st cycle. The capacity retention rate was expressed as an index with the capacity retention rate of battery B1 being 100.

[0132] 《Example 2》

[0133] Batteries A2 to A6 were prepared in the same manner as battery A1 except that the contents of the components in the negative electrode additive were set to the values ​​shown in Table 1. It should be noted that the contents of the components in the negative electrode additive in Table 1 are mass ratios (mass %) relative to the total amount of the negative electrode additive. In Table 1, Li2O and Na2O are oxides of alkali metal elements, and BaO, CaO, and MgO are oxides of Group 2 elements.

[0134] Comparative Example 1

[0135] Battery B1 was produced by the same method as Battery A1, except that the negative electrode mixture did not contain the negative electrode additive and PAA-Li. Battery B2 was produced by the same method as Battery A1, except that the negative electrode mixture did not contain PAA-Li. Battery B3 was produced by the same method as Battery A1, except that the negative electrode mixture did not contain the negative electrode additive. Batteries B4 to B5 were produced by the same method as Battery A1, except that the contents of the components in the negative electrode additive were set to the values ​​shown in Table 1. Batteries B1 to B5 were evaluated by the same method as Battery A1.

[0136] Table 1 shows the evaluation results of batteries A1 to A6 and B1 to B5.

[0137] [Table 1]

[0138]

[0139] In the battery A1 in which the content of the oxide of the Group 2 element (CaO) in the negative electrode additive is less than 20 mass % relative to the total amount of the negative electrode additive, a high capacity retention rate is obtained, and the cycle characteristics are greatly improved. In the battery A1, the improvement in the capacity retention rate relative to the battery B1 is very large, 25%, and the improvement in the capacity retention rate relative to the battery B1 is greatly increased compared with the battery B4 in which the content of the oxide of the Group 2 element (CaO) in the negative electrode additive is 20 mass % or more relative to the total amount of the negative electrode additive. In the battery B4, the improvement in the capacity retention rate relative to the battery B1 is as small as 10%.

[0140] The pH of the negative electrode slurry used in the production of the battery A1 was lower than that of the negative electrode slurry used in the production of the battery B4, and the decrease in pH relative to that of the negative electrode slurry used in the production of the battery B2 was greater.

[0141] In battery A6, in which the content of the oxide of the Group 2 element (BaO) in the negative electrode additive is less than 20 mass % relative to the total amount of the negative electrode additive, the improvement in the capacity retention rate relative to battery B1 is significantly greater than that of battery B5, in which the content of the oxide of the Group 2 element (BaO) in the negative electrode additive is more than 20 mass % relative to the total amount of the negative electrode additive.

[0142] Compared to battery B4 in which the content of oxide of Group 2 element (CaO) in the negative electrode additive is 20% by mass or more relative to the total amount of the negative electrode additive, batteries A2 to A6 in which the content of oxide of Group 2 element (CaO) in the negative electrode additive is less than 20% by mass relative to the total amount of the negative electrode additive also have a significantly greater improvement in the capacity retention rate relative to battery B1. Among them, batteries A1 to A3 in which the content of CaO in the negative electrode additive is 10% by mass or more and 19.5% by mass or less relative to the total amount of the negative electrode additive, a high capacity retention rate of more than 120 is obtained.

[0143] In the battery B1 using the negative electrode mixture that does not contain the negative electrode additive and PAA-Li, a low capacity retention rate is obtained. In the battery B2 in which the negative electrode mixture contains the negative electrode additive but does not contain PAA-Li, the negative electrode additive reduces hydrogen fluoride, and on the contrary, the negative electrode slurry shifts to alkalinity, thereby deteriorating the silicon-containing material, so the cycle characteristics are almost not improved. In the battery B3 in which the negative electrode mixture contains PAA-Li but does not contain the negative electrode additive, PAA-Li acts as a binder, but hydrogen fluoride deteriorates the silicon-containing material, so the cycle characteristics are almost not improved.

[0144] In the negative electrode slurry used in the preparation of battery B2, the negative electrode mixture contained the negative electrode additive, so a higher pH was obtained compared with the negative electrode slurry used in the preparation of battery B1. In the negative electrode slurries used in the preparation of batteries A1 to A6, the negative electrode mixture contained both the negative electrode additive and PAA-Li, so a lower pH was obtained compared with the negative electrode slurry used in the preparation of battery B2.

[0145] 《Example 3》

[0146] Batteries A7 to A8 were prepared and evaluated by the same method as battery A1, except that the contents of the components in the negative electrode additive were set to the values ​​shown in Table 2. The evaluation results are shown in Table 2. It should be noted that the contents of the components in the negative electrode additive in Table 2 are the mass ratios (mass %) relative to the total amount of the negative electrode additive. In addition, in Table 2, Li2O and Na2O are oxides of alkali metal elements, and BaO, CaO and MgO are oxides of Group 2 elements.

[0147] 《Example 4》

[0148] [Preparation of negative electrode material LSX]

[0149] Silica and lithium carbonate were mixed in an atomic ratio of Si / Li of 1.05, and the mixture was calcined in air at 950°C for 10 hours to obtain lithium silicate represented by Li2Si2O5 (z=1 / 2). The obtained lithium silicate was pulverized to an average particle size of 10 μm.

[0150] Lithium silicate (Li2Si2O5) with an average particle size of 10 μm and raw silicon (3N, average particle size of 10 μm) were mixed in a mass ratio of 45:55. The mixture was filled in a pot (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed in the pot, the lid was closed, and the mixture was pulverized at 200 rpm for 50 hours in an inert atmosphere.

[0151] Next, the powdered mixture was taken out in an inert atmosphere, and fired at 800° C. for 4 hours in the inert atmosphere while being pressed by a hot press, thereby obtaining a sintered body of the mixture (negative electrode material LSX).

[0152] After that, the negative electrode material LSX was crushed and passed through a 40 μm sieve, and the obtained LSX particles were mixed with coal tar (MCP250 manufactured by JFE Chemical Co., Ltd.), and the mixture was fired at 800°C in an inert atmosphere to form a conductive layer containing conductive carbon on the surface of the LSX particles. The coverage of the conductive layer was 5% by mass relative to the total mass of the LSX particles and the conductive layer. After that, a sieve was used to obtain LSX particles (average particle size 5 μm) having a conductive layer.

[0153] XRD analysis of the LSX particles revealed that the crystallite size of the silicon particles was 15 nm, calculated using the Scherrer equation based on the diffraction peak attributed to the Si (111) plane. The content of silicon particles in the LSX particles measured by Si-NMR was 55% by mass.

[0154] Batteries C1 to C3 were prepared and evaluated in the same manner as Batteries A1, A7, and A8, except that LSX having the conductive layer obtained above was used as the first composite material among the silicon-containing materials.

[0155] [Table 2]

[0156]

[0157] Batteries A1 and A7 to A8 all achieved high capacity retention rates. Among them, batteries A7 to A8 using the negative electrode additive containing Na2O achieved even higher capacity retention rates of 135 or more.

[0158] Compared with batteries A1 and A7-A8 using SiO as the silicon-containing material, batteries C1-C3 using LSX as the silicon-containing material achieved higher capacity retention rates. Among them, batteries C2-C3 using a negative electrode additive containing Na2O achieved a particularly high capacity retention rate of about 150.

[0159] 《Example 5》

[0160] Batteries A9 to A10 were prepared and evaluated in the same manner as battery A1, except that the PAA-Li content in the negative electrode mixture was set to the value shown in Table 3. It should be noted that the PAA-Li content in Table 3 is the amount (mass parts) per 100 mass parts of negative electrode active material.

[0161] Batteries A11 to A12 were prepared and evaluated in the same manner as battery A1, except that the content of the negative electrode additive in the negative electrode mixture was set to the value shown in Table 3. It should be noted that the content of the negative electrode additive in Table 3 is the amount (mass parts) per 100 mass parts of the negative electrode active material.

[0162] Batteries A9 to A12 were evaluated in the same manner as for Battery A1. The evaluation results are shown in Table 3.

[0163] [Table 3]

[0164]

[0165] Batteries A1, A9, and A10 in which the content of PAA-Li in the negative electrode mixture was 0.2 parts by mass or more and 2.0 parts by mass or less per 100 parts by mass of the negative electrode active material, obtained a high capacity retention rate and improved cycle characteristics. Batteries A1, A11, and A12 in which the content of the negative electrode additive in the negative electrode mixture was 0.3% by mass or more and 7% by mass or less relative to the total amount of the negative electrode mixture, obtained a high capacity retention rate.

[0166] Industrial Applicability

[0167] The nonaqueous electrolyte secondary battery of the present invention is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0168] The present invention has been described in its present preferred form, but the disclosure is not to be construed in a limiting sense. Various modifications and changes will be apparent to those skilled in the art after reading the above disclosure.

[0169] Description of Reference Numerals

[0170] 1: electrode group, 2: positive electrode lead, 3: negative electrode lead, 4: battery case, 5: sealing plate, 6: negative electrode terminal, 7: gasket, 8: sealing plug.

Claims

1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising: a negative electrode mixture comprising a negative electrode active material capable of electrochemically storing and releasing lithium ions, a negative electrode additive, and an acrylic resin, The negative electrode active material comprises a silicon-containing material, The negative electrode additive comprises at least an oxide of a Group 2 element and silicon dioxide, The oxide of the Group 2 element includes at least one selected from the group consisting of BeO, MgO, CaO, SrO, BaO and RaO, The acrylic resin contains at least a (meth)acrylate unit. The content of the oxide of the Group 2 element in the negative electrode additive is less than 20% by mass relative to the total amount of the negative electrode additive. The content of the negative electrode additive in the negative electrode mixture is less than 8 mass % relative to the total amount of the negative electrode mixture.

2. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein The oxide of the Group 2 element includes at least one selected from the group consisting of BaO and CaO.

3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein: The negative electrode additive further comprises an oxide of an alkali metal element, The oxide of the alkali metal element includes at least one selected from the group consisting of Li2O, Na2O and K2O.

4. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 3, wherein: The oxide of the alkali metal element includes Na2O.

5. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1, 2, and 4, wherein The content of the negative electrode additive in the negative electrode mixture is 0.3 mass % or more and 7 mass % or less relative to the total amount of the negative electrode mixture.

6. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1, 2, and 4, wherein The (meth)acrylate salt is a lithium salt of (meth)acrylic acid.

7. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1, 2, and 4, wherein The content of the acrylic resin in the negative electrode mixture is 0.2 parts by mass or more and 2 parts by mass or less per 100 parts by mass of the negative electrode active material.

8. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1, 2, and 4, wherein The silicon-containing material comprises: a composite material having a silicate phase and silicon particles dispersed in the silicate phase, The silicate phase includes at least one selected from the group consisting of alkali metal elements and Group 2 elements.

9. The negative electrode for a non-aqueous electrolyte secondary battery according to any one of claims 1, 2, and 4, wherein The negative electrode active material further includes a carbon material. 10 . The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , comprising: a negative electrode current collector; and a layer supported on a surface of the negative electrode current collector and containing the negative electrode mixture.

11. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The negative electrode is the negative electrode according to any one of claims 1 to 10.

12. The nonaqueous electrolyte secondary battery according to claim 11, wherein: The non-aqueous electrolyte contains LiPF6.

Citation Information

Patent Citations

  • Negative electrode active substance for nonaqueous secondary cell and method for producing the same

    CN102714307A

  • Components for battery cells with inorganic parts with low thermal conductivity

    CN102844908A

  • Negative electrode active material for nonaqueous electrolyte secondary batteries and method for producing same

    CN105849953A

  • Anode compositions for rechargeable batteries and methods of making same

    CN106463714A

  • Negative-electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    CN107210442A